The deficit in cataract surgery in England and Wales and the escalating problem of visual impairment: epidemiological modelling of the population dynamics of cataract. Issue 1 (1st January 2000) - Minassian, D C; Reidy, A; Desai, P; Farrow, S; Vafidis, G; Minassian, A
Abstract : BACKGROUND: The pool of old cases of cataract, the expected new cases, and the shortfall in cataract surgery and consequently the numbers dying with poor vision without the benefit of cataract surgery are regarded as escalating problems worldwide. Successive governments and the professional ophthalmic bodies have not had the wherewithal to estimate the magnitude or interaction of these elements in the population of the UK. This study has collected and applied the best available epidemiological data on cataract prevalence, incidence and service utilisation, and demography to address the problem of control of the cataract pool in the population of England and Wales. METHODS: Data from recent surveys undertaken by the authors, both on prevalence of vision impairing cataract and on patterns of cataract surgery, were used together with demographic and service utilisation information obtained from government departments. These were integrated within a holistic model, which was run under varied assumed levels and patterns of service provision. RESULTS: The study shows that there is a serious pool of unoperated vision impairing cataract in the population aged 65 and older, reflecting a shortfall in cataract surgery. Continuing with the present level and pattern of service provision, the pool will increase to over 2.5 million by the year 2001. In addition, more than 700 000 will die with unoperated impaired vision. CONCLUSIONS: Targeting of existing or new additional operations to those below the visual acuity of 6/12 will have relatively little effect on numbers dying without surgery, but should have a substantial controlling effect on the pool of vision impairing cataract in the population.